Individual Differences - Cooper Colin (Arnold, 1998)
A lively, illustrated, introduction that provides a clear conceptual understanding of the key issues in this field. Preface, Introduction to Individual Differences, Kelly and Rogers, Freud's Psychoanalytical Theory, An Evaluation of Freud's Theories, Trait Theories of Personality, Biological and Social Bases of Personality, The Structure and Measurement of Abilities, Ability Processes, Environmental and Genetic Determinants of Personality and Ability, Mood States and Motivational States, Measuring Individual Differences, Personality Through Introspection: Testing the Theories of Kelly and Rogers, The Reliability and Validity of Psychological Tests, Factor Analysis, Performing and Interpreting Factor Analyses, Item Response Theory, Problems With Tests, Constructing a Reliable Test, Measuring Mood and Motivation, Conclusions, References, Subject and Author Index.